SOSIALISASI DAN PENDAMINGAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA UNTUK MENINGKATKAN PENDAPATAN PELAKU UMKM DI DESA BERCAK, KECAMATAN WONOSAMUDRO, KABUPATEN BOYOLALI - BENI PRABOWO; ALEAN KISTIANI H.S; DONNA SETIAWATI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
This Community Service Program ( KKN ) was held in Bercak Village, Wonosamodro District, Boyolali Regency, with the aim of equipping students with the ability to approach the community and form attitudes and behavior to always be sensitive to problems faced by the community. Empowering the community through various aspects of development as an effort to achieve prosperity. The potential of spotting villages is the number of umkm actors in the village, so the authors hold a main work program "Socialization and Assistance in Making Simple Financial Statements to increase the Income of MSME Players". From the work program, students can find out the potential and problems that exist in Bercak Village. KKN activities have been carried out in accordance with the planned work program. The implementation of individual work programs can be carried out thanks to the support and participation of the community, especially MSME actors in Bercak Village and all programs get good responses from local residents so that they can be completed smoothly.